Critique in practice Renzo Martens' episode III "Enjoy poverty" - Downey, Anthony ca. 20. Jh; Roelandt, Els; Martens, Renzo 1973-; Azulai, Ariʾelah 1962-; Barois de Caevel, Eva 1989-; Van Bogaert, Pieter 1962- (Sternberg Press, 2020)
Investigating the economic value of one of the Democratic Republic of the Congo's most lucrative exports (namely, poverty), Renzo Martens' provocative film 'Episode III: Enjoy Poverty' (2008) remains a landmark intervention into debates about contemporary art's relationship to exploitative economies. The contributors to this publication explore the film's legacy and how it relates to the politics of representation, uses of the documentary form, art criticism, the deployment of humanitarian aid, the impact of extractive forms of globalized capital, and the neoliberal politics of decolonization. The unconventional representation of acute immiseration throughout 'Enjoy Poverty' generated far-from-resolved disputes about how deprivation is portrayed in Western mainstream media and global cultural institutions. Using a range of approaches, this volume reconsiders that portrayal and how the film's reception led Martens to found a long-term program, the Institute for Human Activities
Keywords: Martens, Renzo -- 1973-; Film; Rezeption; Aufsatzsammlung